Residual Strain Monitoring and Dynamic Characteristics of Hybrid Hollow Square Tube with Metal–FRP–Metal Sandwich Walls - Zhao Li; Mingyao Liu; Jintao Wang; Wei Ke (International Journal of Polymer Science)
In order to design and fabricate a novel hollow square tube (HST) for ram structure in machine tools, the hybrid HST with sandwich walls based on steel skins and unidirectional carbon fiber-reinforced polymer (CFRP) composite core is proposed. A detailed co-cured fabrication method with embedded fiber Bragg grating (FBG) sensors for residual strains/stresses determination in a hybrid metal–composite structure is presented. Results reveal that the hybrid HST has undergone complex residual strain history, and the strain rate is about 10 times the cooling rate. The tensile strains in the dwell stage transform into compressive strains in the cooling stage due to the mismatch of the coefficients of thermal expansion of the steel plates and the CFRP composite. A comparison of the residual strains in the cooling phase obtained by FBG sensors with those obtained by theoretical calculation is carried out. Furthermore, the dynamic characteristics of the hybrid HST and the steel HST are tested. The results showed that the damping of the hybrid HST is 586% higher than that of the steel HST, while the hybrid HST has a lower first natural frequency (4.6% reduction) and mass (15.9% weight reduction). The influence of co-cure temperature and cooling rate on the size and state of the residual strains is analyzed, which might be helpful to guide the manufacturing of sandwich structures in machine tools. This novel hybrid HST may be used for online health monitoring and safety evaluation to build intelligent machine tools structures.